Pyrolysis properties of municipal sewage sludge with ZnCl2 activation under the N2 atmosphere. (9th December 2008) - Zhai, Y.B.; Zeng, G.M.; Li, C.T.; Wei, X.X.; , L.F. Wang
The municipal sewage sludge with ZnCl2 activation was pyrolysed to obtain useful porous adsorbents. The thermogravimetric analysis and FTIR methods were used to work out the properties of dried sewage sludge with ZnCl2 activation from the Changsha secondary wastewater-treatment plant. The experimental results showed that three stages of weight loss were observed under the heating rates of 15°C/min and 30°C/min, respectively. And combined with the FTIR, CO2 and H2O appeared at every stage. The experimental data were processed through differential coefficient methods and the different mechanical equations of pyrolysis reaction, and gained the kinetic parameters. The results can be academic references for the pyrolysis of sewage sludge in practice.